(untitled) (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2021)
The aim of this research is to find out the differences in spatial intelligence and microscopic representation of prospective biology teachers in 3D software lectures on plant anatomy using Blender and 3DS Max applications. The research method used was quasi-experimental using the research design of The Matching Only Pretest-Posttest group design group. The population in this study is a prospective biology teacher in the department of biology education faculty of teaching and educational sciences in the academic year 2017/2018 at Siliwangi University who contracted the course of plant anatomy. Sampling is done by purposive sampling techniques as many as 2 classes by looking at the level of activeness in the same learning process. The results showed both classes showed a low spatial intelligence N-Gain category, as well as getting an average value of microscopic representation with a score of 3.7 for the use of 3Ds Max and 3.82 for Blender. The conclusion of this study is that there is no difference in spatial intelligence and microscopic representation of students, in addition students are still having difficulty for those who use max 3Ds software, because it requires a high enough computer specification, so the use of 3-dimensional blender application is more recommended used for aspiring biology teachers who want to make 3D forms of biological objects especially plant anatomy.